The issues of execution of the state budget of the Republic of Kazakhstan 2013-2015g.g. (Journal of Economic Research & Business Administration, 2016)
This article deals with the execution of the state budget. An analysis of the revenue side of the state budget of Kazakhstan for 2013-2015 y.y. state budget is considered in the context of local and national budget. Implementation of the budget – it is the practical implementation of the budget for all specified indicators of its revenue and expenditure sides, the article examined the revenue part of the budget for three years. Implementation of the budget relates to the functions of the executive branch. The analysis done by the execution of the budget. The sources of the state budget are the taxes paid to the budgets of all levels, as well as various types of non-tax revenues. The composition of taxes paid and the procedure of their calculation is determined by the tax legislation, the distribution ratio between the levels of the budget system – the budget law. Recipients are tax authorities, who have personal accounts in banks. The tax authority where the taxpayer is registered, working with a specific territorial treasury authority, deciding with him all the questions on accounting, tax refund and offset.
Keywords: budget; interbudget relations; budget levels.